Towards a digital body: the virtual arm illusion - Slater, Mel; Pérez Marcos, Daniel; Ehrsson, Henrik; Sanchez-Vives, Maria V. (Frontiers in Human Neuroscience, 2008)
The integration of the human brain with computers is an interesting new area of applied neuroscience, where one application is replacement of a person's real body by a virtual representation. Here we demonstrate that a virtual limb can be made to feel part of your body if appropriate multisensory correlations are provided. We report an illusion that is invoked through tactile stimulation on a person's hidden real right hand with synchronous virtual visual stimulation on an aligned 3D stereo virtual arm projecting horizontally out of their shoulder. An experiment with 21 male participants showed displacement of ownership towards the virtual hand, as illustrated by questionnaire responses and proprioceptive drift. A control experiment with asynchronous tapping was carried out with a different set of 20 male participants who did not experience the illusion. After 5 min of stimulation the virtual arm rotated. Evidence suggests that the extent of the illusion was also correlated with the degree of muscle activity onset in the right arm as measured by EMG during this period that the arm was rotating, for the synchronous but not the asynchronous condition. A completely virtual object can therefore be experienced as part of one's self, which opens up the possibility that an entire virtual body could be felt as one's own in future virtual reality applications or online games, and be an invaluable tool for the understanding of the brain mechanisms underlying body ownership.